Emissivity and absorption function measurements of Al2O3 and SiC particles at elevated temperature for the utilization in concentrated solar receivers. (1st September 2020) - Zhao, Wanxia; Sun, Zhiwei; Alwahabi, Zeyad T.
Highlights: Optical properties of the two solar-receiver particles are measured at high temperatures. The emissivity is independent of temperature for both particles and agrees with previous reports. The absorption function varies differently with temperature for the two materials. The temperature and rise time of micro-sized particles under high-flux radiation are calculated. Abstract: Solar thermal receivers collect and can store concentrated solar radiation using solid particles. Solid ceramic particles have shown to be a practical and efficient heat transfer media in solar-particle receivers, however, their emissivity and absorptivity at high temperatures are scarcely reported. This gap has led to large uncertainties in the assessment of solar thermal receivers' efficiency. In this work, an experimental method was developed to measure the emissivity and absorption function of solar particles at elevated temperatures up to 1200 K. Two types of solar particles, aluminum oxide (Al2 O3, ∼95% purity) and silica carbide (SiC, ∼99% purity), were studied, particularly aiming to understand the dependence of emissivity and absorption function on temperature. Using a heat transfer model, the emissivity of particles was evaluated based on the fitting of the cooling rate, while the particle absorption function was obtained by fitting of the heating rate, following a well-controlled heating radiation at 910 nm. It was found that the emissivity values of the two particles are independent of temperature, showing constant values of 0.75 ± 0.015 and 0.92 ± 0.012 for Al2 O3 and SiC respectively, in the temperature from 300 to 1200 K. The absorption function was found to be increased nonlinearly with temperature for Al2 O3, while that of SiC dropped slightly. These absorption functions are specified for 910 nm. Using the evaluated experimental values of emissivity and absorption function, the maximum temperature and the temperature rise time of micro-sized particles (hundreds of micrometers) under different radiation fluxes were simulated taking into account the effect of particle diameter.